The ALFA Roman Pot detectors of ATLAS - Grafstrï¿½m, P. (2019)
The ATLAS Roman Pot system is designed to determine the total proton-proton cross section as well as the luminosity at the Large Hadron Collider (LHC) by measuring elastic proton scattering at very small angles. The system is made of four Roman Pot stations, located in the LHC tunnel in a distance of about 240 m at both sides of the ATLAS interaction point. Each station is equipped with tracking detectors, inserted in Roman Pots which approach the LHC beams vertically. The tracking detectors consist of multi-layer scintillating fibre structures read out by Multi-Anode-Photo-Multipliers.